2019
DOI: 10.1007/s42452-019-0372-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of public open spaces (POS) and landscape quality based on per capita POS index in Delhi, India

Abstract: Public open spaces and green cover are a connection between people and nature and are necessary to retain the quality of the urban landscape. Rapid urban growth and population increase put tremendous pressure on public open spaces, which reduces the quality of the urban landscape. The fast urban growth leads to utilize remaining green and open areas of the city for different purposes. As a result, the size of the urban green and open space is decreasing at an alarming rate. Therefore, the study analyses the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Improved physical and mental health, reduced stress levels, and increased happiness and satisfaction amongst citizens indicate the existence of superior quality greens in the city. Scenarios of degenerating UGS quality are well reported across many cities [17]. The city of Bengaluru in India has seen a decrease of 78% in green cover over the course of four decades, along with its deteriorating quality.…”
Section: Degenerating Qualitymentioning
confidence: 99%
“…Improved physical and mental health, reduced stress levels, and increased happiness and satisfaction amongst citizens indicate the existence of superior quality greens in the city. Scenarios of degenerating UGS quality are well reported across many cities [17]. The city of Bengaluru in India has seen a decrease of 78% in green cover over the course of four decades, along with its deteriorating quality.…”
Section: Degenerating Qualitymentioning
confidence: 99%
“…In the specific case of the Di An City (Figure 6), vegetation cover per capita in the An Binh commune was about 3 to 4 times lower than the national standard for green spaces per capita in the class-3 urban (9-11 m 2 person -1 ). This is also 3.6 times lower than the World Health Organization (WHO) standard which set a minimum limit for urban green spaces per capita of 9 m 2 [51]. With the speed of economic growth in this city, the demand for construction would increase.…”
Section: Discussionmentioning
confidence: 81%
“…From earlier studies, we can find general picture of the city where the civic administration must work. For example, in one study of East Delhi, it was found that the area's per capita open space is remarkably less than the prescribed level by the UN and WHO ( Shahfahad et al, 2019 ), in which tehsils 439 (high covid vulnerable) and 440 (moderate covid vulnerable) falls. Open defecation is a major concern in the capital.…”
Section: Resultsmentioning
confidence: 99%